IMPLEMENTASI KONSEP MASJID RAMAH ANAK (MRA) DALAM PERSPEKTIF MANAJEMEN PENDIDIKAN ISLAM : STUDI KASUS DI MASJD JAMI’ AN-NI’MAH KOTA PALU - Rifaldi Rifaldi; Saude BA; A. Markarma (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
ABSTRACT Mosques serve not only as places of worship but also as centers of Islamic education that support children's moral, spiritual, and social development through a safe, comfortable, and child-friendly environment. Although the concept of a Child-Friendly Mosque has received increasing attention, studies examining its implementation from the perspective of Islamic educational management, particularly in managing educational programs for children within mosque settings, remain limited. Therefore, this study is important to provide empirical evidence regarding the management of mosque-based child-friendly education. This study aims to describe the implementation of the Child-Friendly Mosque concept at Jami' An-Ni'mah Mosque in Palu City from the perspective of Islamic educational management and to analyze the supporting and inhibiting factors affecting its implementation. This research employed a qualitative approach using a case study design. The research participants consisted of the mosque administrators, Qur'anic Learning Center (Taman Pendidikan Al-Qur'an/TPA) teachers, parents, and community members involved in the implementation of the Child-Friendly Mosque program. Data were collected through observations, interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing. The trustworthiness of the data was ensured through source triangulation and technique triangulation. The findings revealed that the implementation of the Child-Friendly Mosque concept was realized through various religious educational programs supported by a safe and comfortable learning environment as well as child-friendly instructional approaches. The successful implementation was supported by the active involvement of mosque administrators, TPA teachers, parents, and the local community, while the main challenges included limited facilities, financial resources, and variations in children's concentration during learning activities. The study concludes that the implementation of the Child-Friendly Mosque concept has been carried out effectively; however, further improvements are needed in program planning, organizing, implementation, and evaluation to ensure a more systematic and sustainable mosque-based educational management model. The findings are expected to serve as a reference for the development of Child-Friendly Mosques in other regions. ABSTRAK Masjid memiliki fungsi strategis sebagai pusat ibadah sekaligus pusat pendidikan Islam yang berperan dalam mendukung perkembangan karakter dan spiritual anak. Meskipun konsep Masjid Ramah Anak semakin banyak dikembangkan, kajian yang menganalisis implementasinya dari perspektif manajemen pendidikan Islam, khususnya pada pengelolaan program pendidikan anak di lingkungan masjid, masih relatif terbatas. Oleh karena itu, penelitian ini penting dilakukan untuk memberikan gambaran empiris mengenai pengelolaan pendidikan berbasis masjid yang ramah anak. Penelitian ini bertujuan mendeskripsikan implementasi konsep Masjid Ramah Anak di Masjid Jami’ An-Ni’mah Kota Palu dalam perspektif manajemen pendidikan Islam serta menganalisis faktor pendukung dan penghambat implementasinya. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus. Subjek penelitian terdiri atas pengurus Masjid Jami’ An-Ni’mah, guru Taman Pendidikan Al-Qur'an (TPA), orang tua, dan jamaah yang terlibat dalam pelaksanaan program Masjid Ramah Anak. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi, kemudian dianalisis menggunakan teknik reduksi data, penyajian data, dan penarikan kesimpulan dengan uji keabsahan melalui triangulasi sumber dan triangulasi teknik. Hasil penelitian menunjukkan bahwa implementasi konsep Masjid Ramah Anak diwujudkan melalui penyelenggaraan berbagai program pembinaan keagamaan yang didukung oleh lingkungan belajar yang aman, nyaman, serta pendekatan pembelajaran yang ramah anak. Keberhasilan implementasi didukung oleh keterlibatan pengurus masjid, guru TPA, orang tua, dan masyarakat, sedangkan kendala yang dihadapi meliputi keterbatasan sarana, pendanaan, dan variasi konsentrasi anak selama kegiatan berlangsung. Penelitian ini menyimpulkan bahwa implementasi konsep Masjid Ramah Anak telah berjalan dengan baik, namun masih memerlukan penguatan pada aspek perencanaan, pengorganisasian, pelaksanaan, dan evaluasi program agar pengelolaan pendidikan berbasis masjid dapat berlangsung secara lebih sistematis, berkelanjutan, dan dapat menjadi rujukan bagi pengembangan masjid ramah anak di berbagai daerah.